2019
DOI: 10.1186/s12934-019-1234-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a highly stable α-galactosidase from thermophilic Rasamsonia emersonii heterologously expressed in a modified Pichia pastoris expression system

Abstract: BackgroundStructurally stable α-galactosidases are of great interest for various biotechnological applications. More thermophilic α-galactosidases with high activity and structural stability have therefore to be mined and characterized. On the other hand, few studies have been performed to prominently enhance the AOX1 promoter activity in the commonly used Pichia pastoris system, in which production of some heterologous proteins are insufficient for further study.ResultsReGal2 encoding a thermoactive α-galacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The transcription of pAOX1, pDAS1, and pDAS2 in the presence of Mxr1 (containing S215A mutant) was decreased up to 60% which indicated that Mxr1 exclusively regulates the transcription of pAOX1, pDAS1, and pDAS2. 56 An et al 51 investigated the regulation of modified pAOX1 and simultaneous fortified expression of Mxr1 that is involved in pAOX1 transcription activation for the production of sufficient amounts of a thermo-active ⊍-galactosidase from Rasamsonia emersonii (ReGal2). The expression of ReGal2 in the engineered P. pastoris enabled the production of suitable www.soci.org H Ullah et al…”
Section: Aox1 Promotermentioning
confidence: 99%
“…The transcription of pAOX1, pDAS1, and pDAS2 in the presence of Mxr1 (containing S215A mutant) was decreased up to 60% which indicated that Mxr1 exclusively regulates the transcription of pAOX1, pDAS1, and pDAS2. 56 An et al 51 investigated the regulation of modified pAOX1 and simultaneous fortified expression of Mxr1 that is involved in pAOX1 transcription activation for the production of sufficient amounts of a thermo-active ⊍-galactosidase from Rasamsonia emersonii (ReGal2). The expression of ReGal2 in the engineered P. pastoris enabled the production of suitable www.soci.org H Ullah et al…”
Section: Aox1 Promotermentioning
confidence: 99%
“…Hence, thermophilic fungi which are capable of secreting high yields of thermostable enzymes have gained considerable interest. One such thermophilic fungus R. emersonii has been reported to contain several lignocelluloytic enzymes including endo-1,4-β-glucanase, β-glucosidase, α-galactosidase, xylanase and amylases [3,5,6], thus possessing great industrial and biotechnological potential.…”
Section: Introductionmentioning
confidence: 99%
“…α-Galactosidase production and activity have been reported in fungi, bacteria, plants, and insects. Most known α-galactosidases belong to glycoside hydrolase (GH) families 27 and 36 . Some α-galactosidases are specific for 4-nitrophenyl α-galactopyranoside ( p NPG), 2-nitrophenyl β-D-galactopyranoside, 4-nitrophenyl β-D-glucuronide, melibiose, maltose, raffinose, or stachyose, , and some had high enzyme activity for polymers guar gum, locust bean gum, carob galactomannan, or gum arabic. , …”
Section: Introductionmentioning
confidence: 99%